Sastra Indonesia Dan Perubahan Sosial: Refleksi Historis Dan Kontemporer - Diana (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2025)
This article explores the dialectical relationship between Indonesian literature and social change through historical and contemporary reflections. Using a qualitative-interpretive approach and the framework of the sociology of literature, this study analyzes key literary works from various significant periods, ranging from the national awakening era, the New Order, to the post-Reformasi (Reformation) era. The analysis reveals that Indonesian literature functions not only as a passive mirror reflecting social reality but also as an active agent that shapes discourse, voices criticism, and even articulates resistance against hegemonic power. From its role in shaping national identity, serving as a voice of subtle resistance, to its current exploration of the complexities of gender, identity, and modernity, Indonesian literature has proven to be both a barometer and a vital space for the nation's socio-cultural discourse.